(untitled) (Texas Journal of Medical Science, 2022)
Hypertensive disorder of pregnancy is one of the most common complications in pregnancy forming a triad together with hemorrhage and infection. It affects about 10% of pregnancies and contributes for a significant maternal and perinatal mortality.